THE ESSENCE OF THE AUTHORITY OF THE NOTARY’S HONOR ASSEMBLY IN THE ENFORCEMENT OF CRIMINAL LAW AGAINST NOTARY CONSUMERED CRIMINAL ACTS IN IMPLEMENTING ITS POSITION - Peter Jeremiah Setiawan; Asa Intan Primanta; Gandhis Nawang Wulan; Bagas Mullanda Saputra (Jurnal Hukum dan Kenotariatan, 2021)
One of the new provisions in Law 6/2014 is the presence of the Notary Honorary Council. There are a) it is necessary to take a photocopy of the Minutes of Dead and/or the letters attached to the Minutes of Deeds or Protocols of Notary in the Notary’s deposit; and b) call the Notary to be present of the examination related to the Notary Deed or Protocol is in the Notary’s custody, it must be with the permission of the Notary Honorary Council. It creates a dilemma in society and it is considered a form of impunity for notaries. The formulation of this research are First, what is the classification of criminal acts committed by a notary whose examiner requires the approval of an Honorary Maejis and Second, what is the essence of the authority of the Notary Honorary Council as regulated in Article 66 of Law 2/2014? This research is a legal research with a statute approach and conceptual approach. The result of this research are First, the classification of criminal acts committed by notaries whose examiner requires approval from the Honorary maejis is related to the deed or Notary Protocol is in the notary’s repository. Second, the essence of the authority of the Notary Honorary Council as regulated in Article 66 UU 2/2014 is to provide legal protection for Notaries, Parties who make deeds, and of course third parties (society) who are litigating.